2005
DOI: 10.1007/s00572-005-0017-6
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi associated with the Meliaceae on Hainan island, China

Abstract: Species richness, spore density, frequency of occurrence, and relative abundance of AM fungi were determined in rhizosphere soil samples from nine tropical rainforest sites on Hainan island, south China, and the arbuscular mycorrhizal (AM) status of members of the Meliaceae was examined. All 28 plant taxa investigated (25 species including two varieties of 1 species and three varieties of another) were colonized by AM fungi. The mean proportion of root length colonized was 56% (range 10-95%). Vesicles were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
11
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 38 publications
9
11
2
4
Order By: Relevance
“…The dominance of AMF in tree peony was also in agreement with the observations documented for other horticultural plants in previous studies (Guo et al, 2007;Guo and Liu, 2010;Bechem and Alexander, 2012;Yamato et al, 2012). The occurrence frequency of arbuscules in all cultivars except for HQW in the Xibei cultivar group was lower than that of vesicles, which is in accord with our studies in other plant species or ecosystems (Shi et al, 2006a(Shi et al, , 2006b(Shi et al, , 2007. One possible reason is the characteristic of arbuscules being short-lived, which is related to the absorption and storage of soil nutrients (Shi et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The dominance of AMF in tree peony was also in agreement with the observations documented for other horticultural plants in previous studies (Guo et al, 2007;Guo and Liu, 2010;Bechem and Alexander, 2012;Yamato et al, 2012). The occurrence frequency of arbuscules in all cultivars except for HQW in the Xibei cultivar group was lower than that of vesicles, which is in accord with our studies in other plant species or ecosystems (Shi et al, 2006a(Shi et al, , 2006b(Shi et al, , 2007. One possible reason is the characteristic of arbuscules being short-lived, which is related to the absorption and storage of soil nutrients (Shi et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…The AM fungal diversity that we observed in the different cultivar groups was similar to that of a study done by Guo et al (2007) in the Zhongyuan cultivar group and other ecosystems such as grassland (Gai et al 2009), and these levels of fungal diversity are lower than that of a forest ecosystem (Shi et al, 2006a). Two possible explanations could be (1) the effect of the diversity of host plants and (2) the influence of long-term fertilization.…”
Section: Discussionsupporting
confidence: 89%
“…Cuervo & Rivas (2007) indicated that the number of spores and the colonization percentage are indicators of AMF establishment in roots, but they do not indicate the mycorrhizal effectiveness on host. Shi et al (2006) referred that when the AMF species richness is greater, the root colonization percentage is higher too, regardless the spore number in the soil. For L. styraciflua the number of spores found in the AMF rhizosphere at field conditions might indicate that the native mycorrhizal inoculum has high infectivity in roots as it was observed in the sample nine (> 50% colonization).…”
Section: Discussionmentioning
confidence: 99%
“…Species richness (SR), relative abundance (RA) and isolation frequency (IF) of AMF were expressed as follows: species richness was determined for each of the ten sites; relative abundance was the number of AMF spores of a species divided by the total spores in a season ×100; and isolation frequency was the number of sites where the AMF species was observed divided by the total number of sites ×100 (Shi et al 2006). In addition, AMF diversity was evaluated through Simpson's index of dominance:…”
Section: Distribution Of Amf Spores and Diversity Indexmentioning
confidence: 99%